What is the digestibility and caloric value of different botanical parts in corn residue to cattle?1. (23rd April 2019) - Petzel, Emily A; Titgemeyer, Evan C; Smart, Alexander J; Hales, Kristin E; Foote, Andrew P; Acharya, Subash; Bailey, Eric A; Held, Jeffrey E; Brake, Derek W
Abstract: Two experiments were conducted to measure rates of ruminal disappearance, and energy and nutrient availability and N balance among cows fed corn husks, leaves, or stalks. Ruminal disappearance was estimated after incubation of polyester bags containing husks, leaves or stalks in 2 separate ruminally cannulated cows in a completely randomized design. Organic matter (OM) that initially disappeared was greatest for stalks and least for husks and leaves ( P < 0.01), but amounts of NDF that initially disappeared was greatest for husks, intermediate for stalks, and least for leaves ( P < 0.01). Amounts of DM and OM that slowly disappeared were greatest in husks, intermediate in leaves, and least in stalks ( P < 0.01). However, amounts of NDF that slowly disappeared were greatest in leaves, intermediate in husks, and least in stalks ( P < 0.01). Rate of DM and OM disappearance was greater for leaves, intermediate for husks and least for stalks, but rate of NDF disappearance was greatest for stalks, intermediate for leaves, and least for husks ( P < 0.01). Energy and nutrient availability in husks, leaves, or stalks were measured by feeding ruminally cannulated cows husk-, leaf-, or stalk-based diets in a replicated Latin square. Digestible energy lost as methane was less ( P = 0.02) when cows were fed leaves in comparison to husks or stalks, and metabolizable energy (Mcal/kg DM) was greater ( P = 0.03) when cows were fed husks and leaves compared with stalks. Heat production (Mcal/d) was not different ( P = 0.74) between husks, leaves, or stalks; however, amounts of heat produced as a proportion of digestible energy intake were less ( P = 0.05) among cows fed leaves in comparison to stalks or husks. Subsequently, there was a tendency ( P = 0.06) for net energy available for maintenance from leaves (1.42 Mcal/kg DM) to be greater than stalks (0.91 Mcal/kg DM), and husks (1.30 Mcal/kg DM) were intermediate. Nitrogen balance was greater when cows were fed leaves, intermediate for husks, and least for stalks ( P = 0.01). Total tract digestion of NDF was greater ( P < 0.01) for husks and leaves compared with stalks. Husks had greater ( P = 0.04) OM digestibility in comparison to stalks, and leaves were intermediate. Apparently, greater production of methane from husks in comparison to leaves limited amounts of energy available for maintenance from husks even though total-tract nutrient digestion was greatest when cows were fed husks or leaves.